Prevalence of Viral Hepatitis in Patients attending Medical Camp (Medical Forum Monthly, 2024)
Objective: Objective of this study was to check prevalence of Viral Hepatitis in Patients attending Medical Camp Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted in free Medical Camp of Shaheed Mohtarma Benazir Bhutto Medical University Larkana from 01.07.2011 to 31.12.2011.Materials and Methods: An advertisement was given one week prior via media for awareness of people. The camp was organized by the faculty of Medical unit III on 1st July 2011. This camp, apart from necessary medicines, equipped with diagnostic facilities to diagnose hepatitis B & C viruses. Patients willing to participate in this study were enrolled; patients with known hepatitis B & C were excluded. ELISA technique was used to diagnose. This study was approved by Ethical committee of Shaheed Mohtrama Benazir Bhutto Medical University. SPSS version 19 was used for data analysis.Results: Total of 400 peoples were seen at the camp, 96 of them were already known cases of hepatitis B and C and were excluded from analysis. Of 304 patients 246 were males and 154 were females. From 304 patients 32 (10.5%) patients had hepatitis C and 16 (5.3%) had hepatitis B and rest were seronegative. The frequency of HCV and HBV was common in patients with age between 20 to 40 years.Conclusions: This was a small effort to increase awareness in local population regarding the course of viral hepatitis. We also collected data regarding present prevalence of chronic viral hepatitis in rural areas of interior Sindh. Much more is to be done to control this misery of our community.